Israel : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
This 2004 Article IV Consultation highlights that Israel's economic recovery is under way after a prolonged recession. Growth is being supported by more favorable global economic conditions, an improvement in the security situation, and appropriate policies, which have included tightening the fiscal stance and easing monetary policy. Real GDP grew by an estimated 4.3 percent in 2004, with exports and private consumption leading the way. The economy is expected to continue to strengthen, albeit at a slightly lower growth rate in 2005.